The Illocutionary Acts Found in Main Characters’ Conversation of the Maleficent Movie - Dewi, Ketut Setia; Komang Dian Puspita Candra (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this study is to explore the types of illocutionary acts and the context of situations in each utterance within the Maleficent movie. The study is grounded in Searle's (1979) theory on illocutionary act types and Halliday and Hasan's (1989) theory on situational context. The analysis was carried out using a descriptive qualitative approach. To gather the data, the researcher employed an observation method, which involved watching the Maleficent movie multiple times and taking notes on the main characters' utterances. After gathering the data, the researcher analyzed it in a series of procedures, including categorizing the illocutionary acts by kind and determining the context of each situation. The results of this investigation revealed 39 utterances that suggest illocutionary acts. The following is the result of this study: directives have the highest frequency of occurrence (30.8 %) with 12 utterances. It is followed by commissive (11 utterances, 28.2%), assertive (10 utterances, 25.6%), expressives (4 utterances, 10.3%), and declaratives (2 utterances, 5.1%).